Stepping-stones : a journey through the Ice Age caves of the Dordogne - Desdemaines-Hugon, Christine, 1946- (Yale University Press, 2010)
Over more than twenty-five years of teaching and research, Christine Desdemaines-Hugon has become an unrivaled expert in the cave art and artists of the Dordogne region. In her new book she combines her expertise in both art and archaeology to convey an intimate understanding of the "cave experience." Her keen insights communicate not only the incomparable artistic value of these works but also the near-spiritual impact of viewing them for oneself.-publisher description